Directional sound beam emission from a configurable compact multi-source system - Jiajun Zhao (Nature Portfolio, 2018)
Abstract We propose to achieve efficient emission of highly directional sound beams from multiple monopole sources embedded in a subwavelength enclosure. Without the enclosure, the emitted sound fields have an indistinguishable or omnidirectional radiation directivity in far fields. The strong directivity formed in the presence of the enclosure is attributed to interference of sources under degenerate Mie resonances in the enclosure of anisotropic property. Our numerical simulations of sound emission from the sources demonstrate the radiation of a highly directed sound beam of unidirectional or bidirectional patterns, depending on how the sources are configured inside the enclosure. Our scheme, if achieved, can solve the challenging problem of poor directivity of a subwavelength sound system, and can guide beam forming and collimation by miniaturized devices.